Natural radionuclides in plants, soils and sediments affected by U-rich coal mining activities in Brazil - Galhardi, Juliana Aparecida [UNESP]; Garcia-Tenorio, Rafael; Bonotto, Daniel Marcos [UNESP]; Frances, Inmaculada Diaz; Motta, Joao Gabriel (Elsevier B.V., 2017)
Mining activities can increase the mobility of metals by accelerating the dissolution and leaching of minerals from the rocks and tailing piles to the environment and, consequently, their availability for plants and subsequent transfer to the food chain. The weathering of minerals and the disposal of coal waste in tailing piles can accelerate the generation of acid mine drainage (AMD), which is responsible for the higher dissolution of metals in mining areas. In this context, the behavior of U, Th and K in soils and sediment, and the transfer factor (TF) of U-238, U-234 and Po-210 for soybean, wheat, pine and eucalyptus cultivated around a coal mine in southern Brazil was evaluated. Alpha and gamma spectrometry were used for the measurements of the activity concentration of the radioelements. Po-210 was the radionuclide that is most accumulated in the plants, especially in the leaves. When comparing the plant species, pine showed the highest TF values for U-234 (0.311 +/- 0.420) for leaves, while eucalyptus showed the highest TF for U-238 (0.344 +/- 0.414) for leaves. In general, TF were higher for the leaves of soybean and wheat when compared to the grains, and grains of wheat showed higher TF for Po-210 and U-238 than grains of soybean. Deviations from the natural U isotopic ratio were recorded at all investigated areas, indicating possible industrial and mining sources.of U for the vegetables. A safety assessment of transport routes and accumulation of radionuclides in soils with a potential for cultivation is important, mainly in tropical areas contaminated with solid waste and effluents from mines and industry. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Biomonitoring; Coal mining; Uranium; Thorium; Polonium